Relationship between Knowledge and Health Behavior about Menstruation of Students at SMAN 3 Padang Panjang - Cici Rahayu; Ardi Ardi; Ratna Lestari (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2022)
Adolescence is a period of transition from childhood to adulthood marked by physical and psychological changes. One of the physical changes in the occurrence of secondary sex changes, namely menstruation. Knowledge of health behavior during menstruation is important to form correct health behavior during menstruation. The problems that arise are the knowledge of female students about menstruation varies, the lack of understanding of female students in maintaining body and genital hygiene during menstruation, and the lack of understanding of students in maintaining diet and exercising during menstruation. This was obtained from the results of observations by distributing questionnaires to female students of class XI science. This study aims to determine the relationship between knowledge and health behavior about menstruation of students at SMAN 3 Padang Panjang. This research is descriptive research. The population of this study was all students of class XI science at SMAN 3 Padang Panjang in the 2020/2021 academic year. The research sample amounted to 61 people with the saturation sampling technique. The research instrument used a knowledge test and a health behavior questionnaire. The results showed that knowledge of menstruation and the health behavior of students was included in the sufficient category with an average of 50 and 64, there was a positive and significant correlation between knowledge and health behavior of students in class XI with a value of r = 0, 460; the coefficient of the t-count value is 3.9792, which is greater than the t-table coefficient, which is 2.00100. So it can be concluded that there is a positive and significant relationship between knowledge of menstruation and the health behavior of students at SMAN 3 Padang Panjang.